Participation in lung cancer screening programs: are there gender and social differences? A systematic review - Stefanie Schütte; Damien Dietrich; Xavier Montet; Antoine Flahault (Frontiers Media S.A., 2018)
Abstract Lung cancer remains the leading cause of cancer mortality worldwide. A number of screening trials for early detection of lung cancer exist, using chest X-ray, low-dose computed tomography, or both. However, little is known about the socio-demographic characteristics of participants in lung cancer screening programs. As gender and socio-economic determinants are important variables to consider for successful program implementation, this review aims to characterize the participants in such programs and to investigate whether differences in representation exist across screening programs. Systematic methods were used to identify relevant studies. A search was undertaken to locate all studies published up to August 2017 assessing the socio-demographic profile of participants in lung cancer screening programs. A search strategy was developed, refined, and implemented to search in two different online databases (MEDLINE and Web of Sciences). A total of 1588 references were retrieved of which 14 were eligible for review. The results highlight differences in gender and social characteristics of participants across programs, while noting that differences may be partly explained by the various epidemiological contexts, program inclusion criteria, and socio-economic status (SES) measures collected. Most importantly, despite a well-recognized predominance of low SES among heavy smokers, people with high SES are seemingly over-represented among participants. Male participants also seem to be over-represented. These findings are important to help inform the development and implementation processes of future lung cancer screening programs, which should likely include strategies for engaging women as well as individuals with low SES and, of course, those most at risk for developing lung cancer.